International relations theories : discipline and diversity - Dunne, Timothy , 1965-; Kurki, Milja; Smith, Steve , 1952- (Oxford University Press, 2013)
Drawing on a wealth of expertise from a global team of contributors, the third edition of International Relations Theories provides an up-to-date and comprehensive account of all the major IR theories--including some of the more alternative understandings not found in other texts--and supports them with case study examples